2020
DOI: 10.7554/elife.55038
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation controls the balance between surface connection and scission of caveolae

Abstract: Caveolae are bulb-shaped invaginations of the plasma membrane (PM) that undergo scission and fusion at the cell surface and are enriched in specific lipids. However, the influence of lipid composition on caveolae surface stability is not well described or understood. Accordingly, we inserted specific lipids into the cell PM via membrane fusion and studied their acute effects on caveolae dynamics. We demonstrate that sphingomyelin stabilizes caveolae to the cell surface, whereas cholesterol and glycosphingolipi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 58 publications
6
57
0
Order By: Relevance
“…These properties, including stimulation by sphingomyelinase, are also associated with MEND, a massive endocytic process detected by electrophysiological approaches ( Hilgemann et al, 2018 ). Interestingly, a recent study ( Hubert et al, 2020 ) confirmed earlier findings that sphingomyelinase treatment stimulates caveolar endocytosis ( Corrotte et al, 2013 ) and suggested that enrichment in glycosphingolipids and cholesterol resulting from sphingomyelin hydrolysis may promote caveolae fission from the PM through lipid phase separation mechanisms.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These properties, including stimulation by sphingomyelinase, are also associated with MEND, a massive endocytic process detected by electrophysiological approaches ( Hilgemann et al, 2018 ). Interestingly, a recent study ( Hubert et al, 2020 ) confirmed earlier findings that sphingomyelinase treatment stimulates caveolar endocytosis ( Corrotte et al, 2013 ) and suggested that enrichment in glycosphingolipids and cholesterol resulting from sphingomyelin hydrolysis may promote caveolae fission from the PM through lipid phase separation mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“…Our results identify EndoA2 as a novel molecular player in the PM remodeling process triggered by these parasites to enter host cells and in the compensatory tubular endocytic pathway that promotes PM repair in the absence of caveolae. In future studies it will be of great interest to investigate whether changes in lipid composition, such as those recently shown to stimulate caveolar endocytosis ( Hubert et al, 2020 ), occur in caveolae and in tubular endosomes associated with PM repair and T. cruzi invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In the past this has been difficult for various endocytic pathways due to their small size and fast dynamics. In fixed cells, however, caveolar vesicles can be distinguished by EM or electron tomography as vesicles containing an enclosed lipid bilayer (Popescu et al, 2006 ; Hubert et al, 2020b ; Matthaeus et al, 2020 ; Webb et al, 2020 ). Novel super resolution imaging techniques such as Stochastic Optical Reconstruction microscopy (STORM) and Stimulated Emission Depletion (STED) microscopy with resolution limits up to 40 nm are also able to identify caveolar vesicles (Platonova et al, 2015 ; Tachikawa et al, 2017 ; Yeow et al, 2017 ; Khater et al, 2018 ; Matthaeus et al, 2019 ).…”
Section: Caveolae Traffickingmentioning
confidence: 99%
“…This is in contrast to clathrin mediated endocytosis where defined cargos and trafficking routes are well-established and mainly accepted. Recent data has suggested that high levels of extracellular cholesterol and glycosphingolipids are able to stimulate caveolar dynamics (Hubert et al, 2020b ). Also, albumin (Minshall et al, 2000 ; Botos et al, 2008 ), okadaic acid and glycosphingolipids (Parton et al, 1994 ; Shvets et al, 2015 ), cholesterol and long-chain fatty acids (Le Lay et al, 2006 ; Hao et al, 2020 ), simian virus 40 (Tagawa et al, 2005 ), and endothelin (Oh et al, 2012 ) are thought to be potential detachment and internalization triggers in some cell types.…”
Section: Caveolae Traffickingmentioning
confidence: 99%
See 1 more Smart Citation